Utilização de energia solar para secagem de microalgas - Silva, João Paulo Siqueira (2017)
The appeal for the use of renewable energy sources increases every day and solar energy is a main alternative because it is abundant, low-cost and totally clean. Spirulina platensis shows great commercial interest due to the search for a healthy food, its excellent nutritional composition and the high amount of bioactive compounds, as is the case of phycocyanin. However, it is a highly perishable biomass because of its high humidity. The objective of the present work is to develop an indirect exposure solar dryer capable of promoting the drying of Spirulina platensis by varying the volumetric flow rate of air and the lowest feed load. The dryer comprised of a solar collector, a drying chamber and a wind extractor utilizes incident solar radiation to heat and promote a biomass industry deposited in the form of long cylindrical pellets in perforated trays in the drying chamber. The solar dryer reduced the humidity of Spirulina platensis to acceptable levels in a short time with an average of 8.77%. It was observed a general degradation of the total phenolic content, the total flavonoid content was influenced by the mass amount, and the best condition for the intermediate feed mass and the phycocyanin content was influenced by the volumetric flow rate of air, where the best condition was minimum flow rate. Finally, the influences of the various variables involved in drying were grouped into a dimensionless drying N and the condition that best meets all the requirements analyzed for a combination of a minimum volumetric air flow rate and an intermediate feed mass of Spirulina platensis.